ON STAUDE S NEW GENERIC NAMES FOR AGARICS - DONK, M. A. (REINWARDTIA, 1954)
The author concludes that the generic names for agarics first introduced by Staude (1857) have been validly published.When I drew attention to Staudes forgotten "Die Schwamme Mittel deutschlands" (1857), I felt obliged to conclude that the new generic names for agarics appearing in that work were validly published (Donk, 1949: 319-320), and I still am fully convinced that this conclusion must be upheld. Rogers (1950: 22) submitted that Staude, although referring to Collybia and other genera as G [attungen], did not definitely accept them as genera, since he continued to refer species under them to Agaricus, thereby implying that they were only subgenera or sections; and that Staude, therefore, dit not validly publish these generic names. Rogerss conclusion is untenable for several reasons. If his argument became generally accepted, quite a lot of generic names might be murdered by it: the number of generic names established without simultaneously published new combinations with the new generic name, like those without any mention of species, is considerable. Such an attitude would not only be undesirable from a practical point of view, but would also disregard the declared object of the Code to promote stability of nomenclature. The Code has deliberately and carefully avoided the stipulation that a new generic name requires simultaneously published new combinations; it has even refused to rule that new generic names ought to be associated with binomials, as was stipulated by the former American code! Certainly this was not done solely to accomodate such special cases as, for example, Tournefortian generic names published after 1753 as an overflow from the pre-binomial period: the decision was for general application. Staude emphatically marked the names in question as generic ones; not only in the introductory pages, but also throughout his more detailed treatment of the agarics he preceded these generic names with "G[attung]" and added generic descriptions.He supplied the information that, "the genera to follow are all according to Fries. Cp. Systema mycologicum